Two new species of Bulbophyllum from Bhutan - Gyeltshen, Phub (Universidad de Costa Rica, 2023)
Two new species of Bulbophyllum, namely, B. gurungianum (sect. Biseta) and B. punakhaense (sect. Brachyrantha) are described and illustrated. Bulbophyllum gurungianum is similar to B. brevispicatum and B. sonii but differs strikingly by having pseudobulbs placed distantly on the rhizome, a shorter peduncle, and oblong petals with a ciliated margin. Bulbophyllum punakhaense is morphologically similar to B. farreri, B. thaiorum, and B. mamillatum, but can be easily distinguished by its larger leaves, pseudobulbs distantly placed on the rhizome, longer peduncle, and oblong-lanceolate petals with shortly papillate margin towards the apex. We provide a detailed description of each species, and information on their distribution, ecology, and conservation status.